Students’ Perspective of Factors Affecting Listening - Xuan, Kan; Simanjuntak, Debora Chaterin (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2017)
The teaching of listening in Indonesia is essential, a process that is considered to be indispensable. This paper explores several factors that affect students’ listening comprehension ability; which are: Limitation of Vocabulary, Teaching Strategy, Limitation of Materials and Equipment, Student’s Listening Anxiety, Exposure towards American English and culture. The main purpose of this research is to determine which factor that significantly affects students’ listening comprehension ability. After going through factor analysis, it is found that the most dominant factor that affects listening comprehension ability is Limitation of Listening Materials and Equipment. This study was conducted in three schools: SMP Negeri 1 Cisarua, Bandung, SMP Negeri III Cisarua, Bandung, SMP Negeri I Parongpong, Bandung. Key Words: Listening Comprehension Ability, Exposure towards American English and Culture